2023
DOI: 10.1186/s12888-023-05274-x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between serum vitamin D and thyroid hormone profiles in male patients with alcohol dependence

Yu Liu,
Yayun Xu,
Yongmei Wang
et al.

Abstract: Background Alcohol dependence (AD) results in several medical problems including vitamin D deficiency and thyroid dysfunction. However, the relationship between these two complications remains unclear. The aim of the present study was to explore the relationship between serum vitamin D and thyroid hormone profiles in male patients with AD. Methods A total of 117 male patients with AD were enrolled. Vitamin D deficiency was defined as serum concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
(18 reference statements)
0
0
1
Order By: Relevance
“…In this study, the prevalence of vitamin D deficiency was greater than the prevalence found in other series of treatment-seeking patients with AUD, as studies from Asia and Northern and Central Europe reported a prevalence ranging from 60% and 75% [ 18 , 19 , 20 , 21 , 22 ]. A recent Spanish study among patients with severe AUD admitted to an internal medicine ward in the Canary Islands reported a prevalence of vitamin D deficiency of 28% [ 23 ].…”
Section: Discussioncontrasting
confidence: 49%
“…In this study, the prevalence of vitamin D deficiency was greater than the prevalence found in other series of treatment-seeking patients with AUD, as studies from Asia and Northern and Central Europe reported a prevalence ranging from 60% and 75% [ 18 , 19 , 20 , 21 , 22 ]. A recent Spanish study among patients with severe AUD admitted to an internal medicine ward in the Canary Islands reported a prevalence of vitamin D deficiency of 28% [ 23 ].…”
Section: Discussioncontrasting
confidence: 49%